(untitled) (Impetus, 2021)
The objectives of the research are to identify the number of students who perform some type of physical activity, describe the type of activity they are doing, determine the days a week they perform it, as well as the duration per day and the main factors for which students do not engage in physical activity. Likewise, know the offer of physical and recreational activities for students, offered at the Turrialba Campus, Atlantic Headquarters, UCR. There was a population of 649 people from 12 different careers, all active students from the Turrialba Campus; randomly 121 students, to whom the instrument was applied with their consent. Through a descriptive statistical analysis, the number and average of people who perform some type of physical activity was determined, which was 65.28%, while 34.71% did not perform physical activity, considering them sedentary.